Gis Approach to Estimation of the Total Phosphorous Transfer in the Pilica River Lowland Catchment - Magnuszewski, Artur; Kiedrzyńska, Edyta; Kiedrzyński, Marcin; Moran, Sharon (Quaestiones Geographicae, 2014)
In this paper, the Pilica River catchment (central Poland) is analyzed with a focus on understanding the total phosphorous transfer along the river system which also contains the large artificial Sulejów Reservoir. The paper presents a GIS method for estimating the total phosphorous (TP) load from proxy data representing sub-catchment land use and census data. The modelled load of TP is compared to the actual transfer of TP in the Pilica River system. The results shows that the metrics of connectivity between river system and dwelling areas as well as settlement density in the sub-catchments are useful predictors of the total phosphorous load. The presence of a large reservoir in the middle course of the river can disrupt nutrient transport along a river continuum by trapping and retaining suspended sediment and its associated TP load. Analysis of the indirect estimation of TP loads with the GIS analysis can be useful for identifying beneficial reservoir locations in a catchment. The study has shown that the Sulejów Reservoir has been located in a subcatchment with a largest load of the TP, and this feature helps determine the problem of reservoir eutrphication